Produksi Obeng Minus-Plus Panjang 160 mm dengan Pegangan Kunci Sok Busi M16, Kapasitas 5 Biji/Jam - Azka Najahaan Arsadani; Syamsul Hadi; Muhammad Rafif Daffa Adz Dzakiru; Muhammad Yusuf Kurniawan; Nabil Iwandaka (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
A pair of minus-plus screwdrivers with motorcycle spark plug socket wrench handles that are often lost/lost is a problem. The production objective is to obtain a pair of minus-plus screwdrivers with a length of 160 mm and an M16 spark plug socket wrench. The production objective is to obtain a pair of minus-plus screwdrivers with a length of 160 mm and an M16 spark plug socket wrench. The production method includes: design of a pair of minus-plus screwdrivers and spark plug socket wrenches; selection of minus-plus screwdriver materials with a diameter of 8 mm and a pipe with a diameter of 16 mm x 90 mm, a thickness of 2 mm for socket wrenches from AISI 1045; forming of plus-minus screwdriver bits; forging socket wrenches into hexagons from 16 mm diameter pipes; drilling through the end of 9 mm diameter pipes; making 20 mm long screwdriver shaft torque retainer; installation of torque retainer tightness on the end of 12 mm inner diameter pipes, finishing of screwdriver shafts and socket wrenches; hot-dip galvanization on screwdriver shafts and socket wrenches; quality inspection, dimensions, and open-close packaging. The production results are a pair of 160 mm long minus-plus screwdrivers, 8 mm diameter screwdriver shaft with M16 spark plug socket wrench, 2 mm thickness of AISI 1045 zinc-coated steel, total manufacturing cost of IDR 22,000/unit, manufacturing duration of 12 minutes/unit which has the impact that a pair of minus-plus screwdrivers and socket wrench can be used and can be stored back in the container.